2018
DOI: 10.1007/s00246-018-1854-3
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism for Improved Exercise Performance in Pediatric Fontan Patients After Cardiac Rehabilitation

Abstract: Patients with a Fontan circulation have impaired exercise capacity. Cardiac rehabilitation (CR) has shown promise in enhancing peak exercise parameters in this population, but an improvement in submaximal exercise has not been consistently demonstrated. We assessed the hypothesis that participation in CR will be associated with more efficient oxygen extraction and ventilation during submaximal exercise. In this prospective study, pediatric Fontans completed two 60 min CR sessions per week for 12 weeks. Cardiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…Exercise training is associated with superior inspiratory muscle performance in the setting of heart failure (HF) and respiratory disease [107,108], and this may be another benefit of particular relevance to those with Fontan physiology. For children with a Fontan circulation, exercise training may improve ventilatory efficiency [106], in keeping with improvements seen in children after an isolated 6-week inspiratory muscle training program [109]. Additional potential benefits of exercise, such as improvements in quality of life, body image, mental health, weight, cardiac function, and endothelial function, have been shown in patients with other conditions [110][111][112][113].…”
Section: Benefits Of Regular Moderate To Vigorous Exercisementioning
confidence: 90%
See 1 more Smart Citation
“…Exercise training is associated with superior inspiratory muscle performance in the setting of heart failure (HF) and respiratory disease [107,108], and this may be another benefit of particular relevance to those with Fontan physiology. For children with a Fontan circulation, exercise training may improve ventilatory efficiency [106], in keeping with improvements seen in children after an isolated 6-week inspiratory muscle training program [109]. Additional potential benefits of exercise, such as improvements in quality of life, body image, mental health, weight, cardiac function, and endothelial function, have been shown in patients with other conditions [110][111][112][113].…”
Section: Benefits Of Regular Moderate To Vigorous Exercisementioning
confidence: 90%
“…The benefits of moderate to vigorous intensity exercise training in people with CHD have been investigated in multiple studies [80,87,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106], with most documenting increased exercise capacity and/or physical activity. Of the studies focussed solely on people with a Fontan circulation [87,96,97,101,105,106], two included a Fontan control group and all but one involved aerobic-based interventions with or without a light resistance component. A 20-week high intensity whole-body resistance training program in a group of 11 adults with a Fontan circulation increased skeletal muscle mass by 2 kg and peak exercise capacity by 10%.…”
Section: Benefits Of Regular Moderate To Vigorous Exercisementioning
confidence: 99%
“…Six studies investigated the effects of a combination of aerobic and resistance exercises. 20,[22][23][24][25][26] Five studies investigated the effects of aerobic training. 9,19,[27][28][29] One of these also added stress management counselling, dietary counselling and education about the heart.…”
Section: Training Programmementioning
confidence: 99%
“…21,28,29 The mean percentage of overall attendance was 79%. All studies reported 25 15 AE 2.7 45 --100 ECC -Sutherland (hospital) 25 16 AE 2.5 33 --67 ECC, 17 LT, 17 AP -Wittekind 26 12 AE 2.8 60 50 3.5 50 ECC, 50 LT -Hedlund 28,39 14.2 AE 3.2 47 -2.4 (1.1-6.4) -0% Laohachai 30 16 AE 2 4 8 5 7 5 AE 2 (3-9) -0% Longmuir 24 9.1 41 33 2.9 87 ECC, 13 LT -Opocher 19 8.7 AE 0.6 10 70 1.7 (1-3) --Studies including adults only:…”
Section: Recruitment Compliance and Drop-outsmentioning
confidence: 99%
“…27 Structured Fontan cardiac rehabilitation has been demonstrated to result in many beneficial changes in the Fontan-palliated patient. 28,29 Although weight loss has not been a specific target of these programmes previously, a reduction in visceral adipose is a likely consequence of sustained rehabilitation, which may manifest benefit by positively impacting Fontan circulatory function.…”
Section: Discussionmentioning
confidence: 99%